Quadriceps muscle strength recovery with the use of high tone power therapy after anterior cruciate ligament reconstruction: a randomized controlled trial - Katarzyna Ogrodzka-Ciechanowicz (BMC, 2021)
Abstract Background There are no scientific reports clearly describing the effectiveness of the High Tone Power Therapy in patients after ACL reconstruction. This caused that in own research an attempt was made to present the possibilities of using the selected method of electrical stimulation in the treatment of an orthopaedic patient. The aim was to assess the effectiveness of electro stimulation of the quadriceps muscle in patients after ACL reconstruction, with the use of High Tone Power Therapy. Methods In randomized controlled trial took part thirty-five men, aged 21–50, after ACL reconstruction. The tests were carried prior to and 6 months following the ACL reconstruction. After the surgery, the patients were randomly divided into experimental group (17 patients) with the High Tone Power Therapy in rehabilitation and control group (18 patients) without the High Tone Power Therapy. Patients were subjected to 6-month rehabilitation. Research tools included the measurement of muscle strength torque, ROM, knee and thigh circumference measurements, the Lysholm and the VAS scale. Results After applying HiToP, the analysis showed a statistically significant improvement of muscle torque (p = 0.041, Es = 3.71), knee circumference (p = 0.039, Es = 1.65), thigh circumference (p = 0.049, Es = 1.26), knee extension (p < 0.001, Es = 2.20) in Experimental group compared to the control group. Only the results of the VAS scale did not differ statistically significantly both within a given group and between groups. Conclusions The results confirm the hypothesis that the use of HiToP in patients after ACLr have a beneficial effect on muscle strength, reduction of joint effusion, muscle mass gain and joint function. The assumption that HiToP significantly reduces pain levels is not supported - the results in both groups are statistically insignificant. Trial registration The research project was retrospectively registered in the Australian New Zealand Clinical Trials Registry (ANZCTR). Date of first registration 11.10.2016. Registration number: ACTRN12616001416482 .